Identifying coastal saline soil management practices to reduce land degradation and increase crop production in Bangladesh (Journal of Bangladesh Academy of Sciences, 2021)
A consecutive three year duration field experiment was carried out to identify which of a suitable mulch material and a planting bed or their combinations potentially reduce salt accumulation in soil and increase snake gourd yield in coastal saline soils. There were nine treatment combinations having three kinds of mulch materials: no mulch (control), rice straw mulch and plastic mulch, and three kinds of planting beds: convex bed, flat bed and concave bed. Plastic mulch reduced electrical conductivity of soil by 32% and increased soil temperature by 23% and gravimetric soil moisture content by 25% over control treatment. Plastic mulch had a fruit yield of 30.73, 28.06 and 26.32 t ha-1, which was 72, 237 and 268 % higher than control treatment in 2018, 2019 and 2020, respectively. The convex bed planting had significantly higher fruit yield than flat bed and concave bed planting. Plastic mulching and convex bed planting may therefore be recommended for reducing soil salinity and improving snake gourd yield in coastal saline regions.Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, 145-159, 2020